Risk factors and treatment responses in patients with vitiligo in Japan—A retrospective large‐scale study. Issue 5 (12th March 2015) - Ohguchi, Ryoko; Kato, Hiroshi; Furuhashi, Takuya; Nakamura, Motoki; Nishida, Emi; Watanabe, Shoichi; Shintani, Yoichi; Morita, Akimichi
Abstract: Vitiligo is a refractory skin disease. To investigate the risk factors and treatment responses of patients with vitiligo in Japan, we recorded and analyzed the details of 713 vitiligo patients (comorbidity, treatment responses, family history, age, and sex) who visited the dermatology clinic of the Nagoya City University Hospital, Nagoya, Japan between January 2004 and August 2010 (mean age, 35.2 years; 302 men, 411 women) using logistic regression analysis. The results are expressed as odds ratios (OR) with 95% confidence interval (CI). Patients were diagnosed with vitiligo [ n = 644; 338 generalized type (47.4%), 170 segmental type (23.8%), and 136 localized type (19.1%)], nevus depigmentosus ( n = 53, 7.4%), halo nevus ( n = 14, 2.0%), and hypomelanosis of Ito ( n = 2, 0.3%). For generalized and localized types, none of the analyzed factors were statistically significant. For the segmental type, antinuclear antibody (OR = 1.005; 95% CI, 1.00–1.01; p < 0.05) and onset age < 14 years were the significant factors in patients between 15 years and 29 years (OR = 0.246; 95% CI, 0.113–0.538; p < 0.001), 30–54 years (OR = 0.0419; 95% CI, 0.0133–0.132; p < 0.001), and >55 years (OR = 0.0171; 95% CI, 0.00333–0.0879; p < 0.001). The treatment response rates for narrow‐band UV‐B, topical vitamin D3, and punch graft (1 mm minigraft) were, respectively, as follows: (1) generalized type: 46.3%, 21.1%, and 38.9%; (2) segmental type: 20.3%, 29.0%, and 77.3%; and (3) localized type: 29.2%, 54.8%, and 73.3%. We report the comorbidities and efficacy rates of these treatments. The response data for these treatments, in particular, would be of assistance to the previous explanations, because there were only a few reports on the response data for these treatments. The appropriate treatment should be selected depending on the type of vitiligo.